2021
DOI: 10.1016/j.drugpo.2020.102966
|View full text |Cite
|
Sign up to set email alerts
|

Harm reduction in the time of COVID-19: Case study of homelessness and drug use in Dublin, Ireland

Abstract: Dublin appears to have performed very well as compared to various scenarios for COVID-19 mortality amongst homeless and drug using populations. The experience, if borne out by further research, provides important lessons for policy discussions on the pandemic, as well as broader lessons about pragmatic responses to these key client groups irrespective of COVID-19. The overarching lesson seems that when government policy is well coordinated and underpinned by a science-driven and fundamentally pragmatic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Globally, this has included changes to drugs harm reduction services, including: designating harm reduction services to be essential [ 46 ]; developing emergency harm reduction plans [ 46 ]; access to COVID-19 screening and testing [ 47 ]; changes to service and medication provision to comply with pandemic guidance [ 41 , 42 , 46 – 56 ]; improved access to naloxone and IEP [ 47 , 50 ]; increased awareness of the need for clean water for injecting [ 57 ]; general guidance about reducing COVID-19 spread in services [ 58 – 60 ]; the need for a ‘safe supply’ of drugs [ 46 ]; and the need for holistic models of care that attend to mental and physical health and housing needs [ 46 ]. While evidence is still emerging on how the pandemic impacted drugs harm reduction, strict lockdown rules have appeared to reduce the number of people accessing IEP and other harm reduction services [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, this has included changes to drugs harm reduction services, including: designating harm reduction services to be essential [ 46 ]; developing emergency harm reduction plans [ 46 ]; access to COVID-19 screening and testing [ 47 ]; changes to service and medication provision to comply with pandemic guidance [ 41 , 42 , 46 – 56 ]; improved access to naloxone and IEP [ 47 , 50 ]; increased awareness of the need for clean water for injecting [ 57 ]; general guidance about reducing COVID-19 spread in services [ 58 – 60 ]; the need for a ‘safe supply’ of drugs [ 46 ]; and the need for holistic models of care that attend to mental and physical health and housing needs [ 46 ]. While evidence is still emerging on how the pandemic impacted drugs harm reduction, strict lockdown rules have appeared to reduce the number of people accessing IEP and other harm reduction services [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with benzodiazepine dependency were offered up to 30 mg of benzodiazepine daily to prevent withdrawals for the period of isolation only. In the homeless sector, over 70 people were commenced on benzodiazepine maintenance treatment [49]. In Ireland, it has been reported that 92% of overdoses where methadone was implicated and 81% of deaths where heroin was implicated involved benzodiazepines predominantly [47].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to record and share key information across care settings is vital for the provision of integrated, effective, and efficient personalised healthcare. The introduction of a national unified Electronic Healthcare Record (EHR) system would significantly advance this endeavour [36] across the whole healthcare system and there are some indicators that the response to the COVID-19 pandemic may expedite this process [37]. Moreover, information technology could be harnessed by clinicians and patients to facilitate more efficient and coordinated care pathways [31] that could improve outcomes for people with SUDs [38].…”
Section: Discussionmentioning
confidence: 99%